"Professional feeling": One early childhood educator's emotional discomfort as a teacher and learner. (October 2013) - Madrid, Samara; Baldwin, Nikki; Frye, Eleanor
Using feminist and poststructuralist accounts of teacher emotion, the analysis presented in this article examines one teacher's emotion as she participated in a 6-month ethnographic study of emotion in her preschool classroom while enrolled in an online graduate course focused on the sociology of childhood and socially just curriculum. Analysis followed the ethnographic procedures of Spradley's Developmental Research Sequence to determine themes and patterns within field notes, audio and video data, interview transcripts, and online course documents. The findings showed that emotional discomfort was a central theme as the teacher considered the children's play in relation to the knowledge acquired in the graduate online course and vice versa. More specifically, the findings revealed the teacher's discomfort and the resulting struggle and ambivalence she encountered as new information about children's social worlds disrupted her prior beliefs, values, and feelings. This study uncovers how emotional discomfort can provide productive grounds for reflection, disequilibrium, and dialogue about early childhood classroom practices.